(untitled) (Proceedings of the International Conference of Community Health and Medical Sciences, 2024)
"Protect yourself, your family, and society with complete immunization" is the national motto of World Immunization Week 2023. This subject is meant to serve as a reminder and inspiration for everyone in society to get immunized in order to protect themselves, their families, as well as the local community. Immunization coverage increased once more to 94.9% in 2022 after falling to 84% during the COVID-19 epidemic. Although this is excellent, more work must be done to achieve the WHO goals of 99% (Ministry of Health 2023). As a result, a faster immunization program is required, especially in regions with low coverage levels. This study intends to examine the factors that affect immunization coverage, specifically in the Toddopuli Public Health Facility’s (Pusat Kesehatan Masyarakat – Puskesmas) region, Makassar. Descriptive analytic methodology is applied by conducting in-depth interviews with informants. Choosing informants with the purposive sampling technique. The important informants are the immunization coordinators at the puskesmas, whereas the major informants are five families with infants or young children who provide vaccinations. According to the findings, the success of the immunization program is significantly influenced by family involvement and the work of immunization officers. Both of these variables are more significant than other factors including parental education level, income, and the distance from the home to immunization services. In order to expand immunization coverage in the upcoming years, it is desired that these two items can be further enhanced in the future.